Circular inter–intra pixels bit-level permutation and chaos-based image encryption - Diaconu, Adrian-Viorel (Information sciences, 2016)
The new image encryption architecture presented in this paper employs a novel circular inter–intra pixels bit-level permutation strategy. This strategy aims to reduce redundancies implied by the Fridrich's structure. The newly proposed scheme was subject to extensive security analyses, including statistical and differential analysis, and information entropy calculation. These highlight a desirable security level provided by the insurance of the coveted confusion and diffusion factors.